Cutaneous Leishmaniasis: Case Series on Pregnancy Outcome - Bitton, Yossi (Open Forum Infect Dis, 2020)
We report the pregnancy outcomes of 6 women with cutaneous leishmaniasis; 5 of these women received topical antileishmenial therapy during gestation with paromomycin plus methylbenzethonium chloride combination ointment and/or sodium stibogluconate intralesional injections. No teratogenic effects were reported. Furthermore, no vertical transmission was observed.